2017
DOI: 10.1016/j.immuni.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The TREM2-APOE Pathway Drives the Transcriptional Phenotype of Dysfunctional Microglia in Neurodegenerative Diseases

Abstract: SUMMARY Microglia play a pivotal role in maintenance of brain homeostasis, but lose homeostatic function during neurodegenerative disorders. We identified a specific apolipoprotein E (APOE)-dependent molecular signature in microglia from models of amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS) and Alzheimer’s disease (AD) and in microglia surrounding neuritic β-amyloid (Aβ) -plaques in human AD brains. The APOE pathway mediated a switch from a homeostatic to neurodegenerative microglia phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

166
2,571
17
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,996 publications
(2,919 citation statements)
references
References 61 publications
166
2,571
17
4
Order By: Relevance
“…The purinergic receptor P2RY12, sensing ADP release from damaged tissue and being necessary for rapid migration of cells to the site of tissue damage , is one of the key markers for the homeostatic phenotype of microglia. In line with this is the nearly complete loss of P2RY12 expression on microglia in active experimental and human inflammatory and neurodegenerative lesions . However, it has been shown that P2RY12 is lost in a major subpopulation of microglia in the normal human brain and it was a surprise that systemic immune activation in sepsis did not lead to a further downregulation of its expression in microglia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The purinergic receptor P2RY12, sensing ADP release from damaged tissue and being necessary for rapid migration of cells to the site of tissue damage , is one of the key markers for the homeostatic phenotype of microglia. In line with this is the nearly complete loss of P2RY12 expression on microglia in active experimental and human inflammatory and neurodegenerative lesions . However, it has been shown that P2RY12 is lost in a major subpopulation of microglia in the normal human brain and it was a surprise that systemic immune activation in sepsis did not lead to a further downregulation of its expression in microglia.…”
Section: Discussionmentioning
confidence: 86%
“…The presence of TMEM119 reactivity in P2RY12 negative microglia suggests that loss of this purinergic receptor is not due to the recruitment of circulating myeloid cells, which differentiate into a microglia‐like morphological phenotype. We have shown previously that the loss of P2RY12 reactivity correlates with the extent of neurodegeneration in human cortex of controls and Alzheimer's disease patients . Thus, neurodegeneration instead of inflammation may be the key trigger for the downregulation of P2RY12 expression on CNS microglia.…”
Section: Discussionmentioning
confidence: 89%
“…Such kinetics of microgliosis are in sharp contrast to mouse models of chronic or severe neurodegeneration in which the resolution of microgliosis is not observed [21, 23, 30]. Notably, bulk RNAseq analysis revealed no change in gene regulation between the lesion and contralateral FN in at 60 d after FNX [43].…”
Section: Resultsmentioning
confidence: 99%
“…TREM2 expression by microglia is known to modulate the inflammatory response by suppression of microglia-mediated cytokine production and secretion, and by regulation of phagocytic pathways that clear neuronal debris (Hsieh et al 2009;Krasemann et al 2017). A recent study by Bogie et al identified a scavenger receptor, collectin placenta 1 (CL-P1), as a novel receptor in the uptake of myelin by microglia ( phagocytes).…”
Section: Microglial Functions Reaction To Cell or Tissue Damage And Pmentioning
confidence: 99%